Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, André; Singh, Amit; Banh, Ngoc Chi; Richter, Birte; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, Britta (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: Artificial Intelligence; Computer Science Applications

Gelingensbedingungen gestaltungsorientierter Schulentwicklung - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (Organisation zwischen Theorie und Praxis)

RELD: A Knowledge Graph of Relation Extraction Datasets - Manzoor, Ali; Saleem, Muhammad; Moussallem, Diego; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (The Semantic Web)

iPDP: On Partial Dependence Plots in Dynamic Modeling Scenarios - Muschalik, Maximilian; Fumagalli, Fabian; Jagtani, Rohit; Hammer, Barbara; Huellermeier, Eyke (Proceedings of the World Conference on Explainable Artificial Intelligence (xAI))

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track - European Conference (ECML PKDD))

On Feature Removal for Explainability in Dynamic Environments - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Proceedings of the European Symposium on Artificial Neural Networks (ESANN))

SHAP-IQ: Unified Approximation of any-order Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (Advances in Neural Information Processing Systems (NeurIPS))

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus D.; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.

Continuous-variable quantum optics and resource theory for ultrafast semiconductor spectroscopy [Invited] - Lüders, Carolin; Barkhausen, Franziska; Pukrop, Matthias; Rozas, Elena; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Optical Materials Express)
This review examines the use of continuous-variable spectroscopy techniques for investigating quantum coherence and light-matter interactions in semiconductor systems with ultrafast dynamics. Special emphasis is placed on multichannel homodyne detection as a powerful tool to measure the quantum coherence and the full density matrix of a polariton system. Observations, such as coherence times that exceed the nanosecond scale obtained by monitoring the temporal decay of quantum coherence in a polariton condensate, are discussed. Proof-of-concept experiments and numerical simulations that demonstrate the enhanced resourcefulness of the produced system states for modern quantum protocols are assessed. The combination of tailored resource quantifiers and ultrafast spectroscopy techniques that have recently been demonstrated paves the way for future applications of quantum information technologies.

Strain-Induced Indirect-to-Direct Bandgap Transition, Photoluminescence Enhancement, and Linewidth Reduction in Bilayer MoTe2 - Yu, Yueyang; Dong, Chuan-Ding; Binder, Rolf; Schumacher, Stefan; Ning, Cun-Zheng (ACS Nano)

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.

Prozessbegleitende Qualitätssicherung digitaler Ressourcen (OER). Ein Ansatz für die Lehrkräftebildung am Beispiel der Entwicklung eines Onlinekursangebotes. - Schulze, Johanna; Herzig, Bardo (Herausforderung Lehrer:innenbildung. Zeitschrift zur Konzeption, Gestaltung und Diskussion)

“I do not know! but why?” — Local model-agnostic example-based explanations of reject - Artelt, André; Visser, Roelof; Hammer, Barbara (Neurocomputing)

Technical Transparency for Robot Navigation Through AR Visualizations - Dyck, Leonie; Beierling, Helen; Helmert, Robin; Vollmer, Anna-Lisa (Companion of the 2023 ACM/IEEE International Conference on Human-Robot Interaction)

Entrained flow SCR using an in-situ synthesis of catalyst particles for a combined flue gas cleaning system - Beimdiek, Janis; Schmid, Hans-Joachim

Neuartige Flugstrom SCR an online synthetisierten, nanoskaligen Katalysatorpartikeln in einem kombinierten Gasreinigungsprozess (Poster) - Beimdiek, Janis; Schmid, Hans-Joachim

Influence of atomization on the particle formation in spray flame pyrolysis (Presentation) - Massopo, Orlando; Tischendorf, Ricardo; Schmid, Hans-Joachim; Fröde, Fabian; Grenga, Temistocle; Pitsch, Heinz; Bieber, Malte; Reddemann, Manuel; Kneer, Reinhold
Keywords: Flame Stability; Particle Sample Extraction; SMPS; Impurities

Einfluss der Zerstäubung auf diePartikelbildung bei der Sprayflammenpyrolyse (Vortrag) - Massopo, Orlando; Tischendorf, Ricardo; Schmid, Hans-Joachim; Fröde, Fabian; Pitsch, Heinz; Reddemann, Manuel; Grenga, Temistocle; Kneer, Reinhold
Keywords: SpraySyn; Flammenspraypyrolyse; Maghemite Nanopartikel; Gas to particle-Syntheseweg; Probennahme; Verunreinigung

Potassium Titanyl Phosphate Material Engineering Boosting Integrated Optical Source Performance - Eigner, Christof; Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine (CLEO 2023)
We study the interaction of gray tracking and DC ionic conductivity in Potassium Titanyl Phosphate (KTiOPO 4 , KTP) and present a novel way to reduce conductivity via a potassium nitrate treatment improving the device quality.